PEMBAHARUAN LOCA ANTARA ATS REPORTING OFFICE DENGAN AIRLINES OPERATOR TERHADAP PENDISTRIBUSIAN FLIGHT PLAN DI PERUM LPPNPI CABANG DENPASAR - Gisca Laurenza Sucipto; Lusiana Dewi Kusumayati; Yeni Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This final project explains the obstacles faced by the author regarding LOCA between the ATS RO unit and the Airlines Operator on flight plan distribution at Perum LPPNPI Denpasar Branch. The absence of regulations regarding the handling of the flight plan has resulted in the ineffectiveness of the flight plan processing in the ATS RO unit, so that problem has an impact on the obstruction of flight traffic flow. The research method that the author uses is descriptive qualitative, data collection methods in the form of observations and interviews regarding the obstacles in distributing and processing flight plans with the location indicator AFIL/ZZZZ which according to the author requires a contingency plan in the form of an action in dealing with this.The results of the research can be seen that the LOCA between ATS RO units and Airlines Operators at Perum LPPNPI Denpasar Branch is not optimal, so an update is needed by adding points containing regulations in the form of coordination steps related to this into the existing LOCA.